2022
DOI: 10.1021/acsami.2c17579
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-Free Nanoplatform via Evoking Pyroptosis and Immune Response against Breast Cancer

Abstract: Pyroptosis, as a novel mode of cell death, has been proven to have impressive antitumor effects. Dying cells undergoing pyroptosis can elicit antitumor immunity by the release of tumor-associated antigens (TAAs) and damage-associated molecular patterns (DAMPs). Accordingly, developing an effective, stable, and controllable nanoplatform that can promote these two side effects is a promising option for cancer therapy. In this study, we designed a carrier-free chemophotodynamic nanoplatform (A-C/NPs) using a co-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…For example, gut microbiota-originated metabolic toxins, such as LPS, can act as PAMPs to activate immune cells [ 123 , 124 ]. In parallel, drug-, smoking-, and circadian rhythm-induced oxidative stress can damage intestinal epithelial cells (IECs), such as Paneth cells and goblet cells, releasing cell debris, calreticulin, heat shock proteins (HSPs) and ATP, which can act as DAMPs to promote the progression of inflammation and subsequent pyroptosis and necroptosis [ 125 , 126 , 127 , 128 ]. Immune cells secrete products that are actively involved in the initiation and preservation of inflammation, leading to gut tissue damage.…”
Section: Inflammatory Response and Oxidative Stress In Ibdmentioning
confidence: 99%
“…For example, gut microbiota-originated metabolic toxins, such as LPS, can act as PAMPs to activate immune cells [ 123 , 124 ]. In parallel, drug-, smoking-, and circadian rhythm-induced oxidative stress can damage intestinal epithelial cells (IECs), such as Paneth cells and goblet cells, releasing cell debris, calreticulin, heat shock proteins (HSPs) and ATP, which can act as DAMPs to promote the progression of inflammation and subsequent pyroptosis and necroptosis [ 125 , 126 , 127 , 128 ]. Immune cells secrete products that are actively involved in the initiation and preservation of inflammation, leading to gut tissue damage.…”
Section: Inflammatory Response and Oxidative Stress In Ibdmentioning
confidence: 99%
“…Tumor regrowth is the main cause of low clinical efficacy and cancer death, and thus, we investigated the influence of IGC/NPs on inhibiting tumor regrowth. A recurrence model of BALB/c mice with CT26 tumor was established by surgery when the tumor reached a volume of 100 mm 3[ 26,27 ] (Figure 5H,I). The drug was given every other day from the 15 th day to 30 th day after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, recent research indicates that oxidative damage induction and programmed cell death can also be useful cancer treatment methods. [50] A significant amount of data has demonstrated that development of nanoparticle-based therapy holds huge potential to modulate redox homeostasis for cancer therapy (Fig. 2).…”
Section: Disturbing Redox Homeostasis By Nanoparticlesmentioning
confidence: 99%